Analisa Potensial Debit Air Pada Bendungan Bandar Sei Jepang Sebagai Pemanfaatan Pembangkit Listrik - Muchsin Harahap; Muhammad Fitra Zambak; Marnida Yusfiani (Fakultas Teknik UMSU, 2021)
The Japanese Bandar Sei River is one of the rivers in Tanjungbalai City with a width of 5.1 km and a width of 6 meters. The river flows into the Asahan River. The river flow can be used as a source of electricity by constructing dams on the river. This is used by the author as a form of studies research. The technique used on this studies is the M.J Mock method to find the value of reliable water discharge and Flow Duration Curva for the probability of water discharge. Based on the findings of the research, the analysis of reliable water discharge calculations obtained from the analysis is 4.93 m3 / second. The potential for water power generated is Theoretical Power: 94 kW, Turbine Power: 130 kW and Generator Power: 116 kW. The average value of evapotranspiration is 150.88 mm.